LncRNA BANCR Promotes Pancreatic Cancer Tumorigenesis via Modulating MiR-195-5p/Wnt/β-Catenin Signaling Pathway. (23rd November 2019) - Wu, Xinquan; Xia, Tianfang; Cao, Meng; Zhang, Pengbo; Shi, Guodong; Chen, Lei; Zhang, Jingjing; Yin, Jie; Wu, Pengfei; Cai, Baobao; Lu, Zipeng; Miao, Yi; et al.
Long noncoding BRAF-activated noncoding RNA has been reported to be tightly associated with tumorigenesis and development in various types of cancers. However, the expression, biological function, and modulatory mechanism of BRAF-activated noncoding RNA in pancreatic cancer remained unclear. In the present work, we explored the carcinogenic activity and underlying mechanism of BRAF-activated noncoding RNA on pancreatic cancer in vitro . We identified that BRAF-activated noncoding RNA was upregulated in pancreatic cancer tissues and cell lines, and BRAF-activated noncoding RNA was related to tumor metastasis and stage. BRAF-activated noncoding RNA reinforces proliferation, invasion, and migration in PANC-1 and SW1990 cells. Moreover, miR-195-5p was downregulated in both PC tissues and cell lines. Our results based on luciferase reporter, RIP-Ago2 and qRT-PCR assays, showed that miR-195-5p was a direct target of BRAF-activated noncoding RNA. Furthermore, miR-195-5p inhibitor abrogated the effects of short-interfering BRAF-activated noncoding RNA on PANC-1 and SW1990 cell growth and invasion in vitro . We further identified that BRAF-activated noncoding RNA played a vital role in activating the Wnt/β-catenin pathway by sponging miR-195-5p. Collectively, our study showed that BRAF-activated noncoding RNA promotes pancreatic cancer tumorigenesis through miR-195-5p/Wnt/β-catenin axis may serve as a potential target for diagnostics and therapeutics in pancreatic cancer.